PERLINDUNGAN HUKUM KORBAN TINDAK PIDANA PENCURIAN RINGAN PADA PROSES DIVERSI TINGKAT PENYIDIKAN - Kaimuddin, Arfan (Jurnal Mahasiswa Fakultas Hukum, 2015)
Absrtact Journal writing in the form of research is motivated by three issues. First, juridical problems that can be observed from the inkonsestensi in Law 11 of 2012 on the SPPA between article 1, paragraph (6) of the restorative justice with Article 9 paragraph (2). This has hurt the concept of restorative justice for victims of crime minor theft. Second, theoretical issues, right of victims to be dilundungi, but in practice these rights neglected. Third, sociological problems that can be observed is that the criminal acts of theft committed by children can interfere with the comfort and safety in the community. For the purpose of this study found the philosophical basis of the formation of Article 9, paragraph (2) of Law No. 11 Year 2012 on SPPA.Untuk outlines how should the diversion of the victims of wage theft losses under local provincial drinking implemented. This journal writing using normative legal research methods. Forming the basis of Article 9 paragraph (2) Article 9 paragraph (2) of Law No. 11/2012 on SPPA there are four main points, three points meant to protect children in order to avoid prison kemmudian fourth point is to protect the interests of victims and perpetrators of child. If the victim does not wish to participate, diversion will still run. Tersbut philosophical basis is contrary to the theory of restorative justice and also the theory of legal protection. After doing a comparison process is versioned with the State Philippines and Malaysia, to achieve the ideal form of diversion for minor criminal offenses of theft committed by children in Indonesia is to use a restorative justice approach in an attempt of diversion. This is supported by the theory of criminal law policy. With reformulate to alter the content of Article 9, paragraph (2) of the Act SPPA. Key words: Diversion, Restorative justice, rights of victims Absrtak Penulisan jurnal berupa hasil penelitian ini dilatarbelakangi oleh tiga permasalahan. Pertama, permasalahan yuridis yang bisa dicermati dari adanya inkonsestensi dalam UU No. 11 tahun 2012 tentang SPPA yakni antara pasal 1 ayat (6) mengenai restorative justice dengan Pasal 9 ayat (2). Hal ini telah mencederai konsep restorative justice bagi korban tindak pidana pencurian ringan. Kedua, permasalahan teoritis, Hak-hak korban harus dilundungi, namun dalam praktek hak tersebut terabaikan. Ketiga, permasalahan sosiologis yang bisa dicermati ialah Tindak pidana pencurian yang dilakukan oleh anak dapat mengganggu kenyamanan danÂ keamanan di dalam masyarakat. Tujuan penelitian ini Untuk menemukan dasar filosofis pembentukan Pasal 9 ayat (2) UU No. 11 Tahun 2012 tentang SPPA.Untuk menguraikan bagaimana semestinya proses diversi terhadap korban pencurian yang kerugiannya dibawah upah minum provinsi setempat dilaksanakan. Penulisan jurnal ini menggunakan metode penelitian hukum normatif. Dasar pembentukan Pasal 9 ayat (2) Pasal 9 ayat (2) UU No. 11/2012 tentang SPPA terdapat empat poin utama, tiga poin bertujuan untuk melindungi anak agar terhindar dari penjara kemmudian poin keempat yaitu melindungi kepentingan korban dan juga pelaku anak. Apabila korban tidak ingin berpartisipasi, diversi tetap akan dijalankan. Dasar filosofis tersbut bertentangan dengan teori restorative justice dan juga teori perlindungan hukum. Setalah melakukan perbandingan Proses diversi dengan Negara Filiphina dan Malaysia, untuk mencapai bentuk ideal diversi untuk tindak pidana pencurian ringan yang dilakukan oleh anak di Indonesia ialah dengan menggunakan pendekatan restorative justice pada upaya diversi. Hal ini didukung oleh teori kebijakan hukum pidana. Dengan mereformulasi untuk merubah isi dari Pasal 9 ayat (2) UU SPPA. Kata kunci: diversi, restorative justice, hak korban